2002
DOI: 10.1086/343741
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Stromal Cell–Derived Factor (SDF)‐1 Levels, SDF1‐3′A Genotype, and Expression of CXCR4 on T Lymphocytes: Their Impact on Resistance to Human Immunodeficiency Virus Type 1 Infection and Its Progression

Abstract: Plasma stromal cell-derived factor (SDF)-1 levels, SDF1-3'A polymorphism, and CXCR4(+) T lymphocytes in relation to resistance to human immunodeficiency virus (HIV)-1 infection and its progression were investigated in a study of HIV-positive patients, exposed but uninfected (EU) subjects, and healthy control subjects, all lacking CCR5 Delta 32 homozygosity. SDF1-3'A homozygosity was associated with low plasma SDF-1 levels in uninfected persons and was not related to long-term nonprogression. HIV-1 infection in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 71 publications
2
86
1
Order By: Relevance
“…In fact, an association between CXCL12-3 0 AA homozygosity and low plasma CXCL12 levels in HIV-exposed, but uninfected, persons was reported by Soriano et al 23 Moreover, Signoret et al 24 showed that the increased secretion of the CXCL12 may downmodulate CXCR4 on CD34 þ cells, a phenomenon that, in turn, prevents the homing of haematopoietic progenitors to the BM. Indeed, we and others 13,25,26 have observed a negative correlation between the mobilization capacity and CXCR4 expression on CD34 þ cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In fact, an association between CXCL12-3 0 AA homozygosity and low plasma CXCL12 levels in HIV-exposed, but uninfected, persons was reported by Soriano et al 23 Moreover, Signoret et al 24 showed that the increased secretion of the CXCL12 may downmodulate CXCR4 on CD34 þ cells, a phenomenon that, in turn, prevents the homing of haematopoietic progenitors to the BM. Indeed, we and others 13,25,26 have observed a negative correlation between the mobilization capacity and CXCR4 expression on CD34 þ cells.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, our results regarding patients undergoing autologous transplantation of haematopoietic stem cells concur with those reported by Benboubker et al 15 The association between the CXCL12 gene polymorphism and the serum levels of CXCL12vwas suggested by Winkler et al 11 However, to date, the exact relationship between the CXCL12 genotypes and the corresponding protein production is not clear and the studies examining the association differ in their methodological approaches. [20][21][22][23] As this mutation lies in the 3 0 UTR of the gene, Winkler et al 11 suggested that this mutation may upregulate transcription of the gene, resulting in more abundant CXCL12, which in turn, inhibits T-tropic HIV-1 and delays the onset of the disease. Arya et al 20 tested this hypothesis in vitro: the wild-type and the mutant CXCL12 gene were cloned and the expression was measured in human and insect cells in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Soriano et al have shown an association between high plasma SDF-1 levels and the SDF-1 A allele [31]. However, other studies demonstrated that SDF-1, at least in high concentrations, may mediate anti-inflammatory and matrix-stabilizing effects in unstable angina.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,20 In addition, studies that examined the relationship between circulating levels of SDF-1 and HIV-1 disease progression have obtained contrasting results. [21][22][23] Similarly, other reports have proposed conflicting roles for SDF-1 in neuronal survival and apoptosis in patients with HIV-1 encephalitis. [24][25][26][27] Molecular genetic epidemiological studies have identified polymorphisms in more than 20 human genes, including several chemokines and their receptors, that are associated with HIV-1 infection and/or AIDS disease pathogenesis.…”
Section: Introductionmentioning
confidence: 97%